Collaborative Governance in the Implementation of Electronic Government-Based Public Information Openness in Kraton Village, Yosowilangun District, Lumajang Regency - Mindarti, Lely Indah; Mustofa, Mochammad Zainal; Imam, Muhammad (Universitas 17 Agustus 1945 Surabaya, 2024)
Public Information Transparency (KIP) is crucial in achieving Good Governance. This study focuses on implementing KIP through electronic government in Kraton Village, Yosowilangun District, Lumajang Regency, where most residents are employed in agriculture and trade, posing challenges to the implementation of electronic KIP. Employing qualitative descriptive research, this study analyzes data using the interactive data analysis model developed by Miles, Huberman, and Saldana. The findings reveal a beacon of success in Kraton Village, where KIP has been effectively implemented through electronic government. Mandatory information is disseminated seamlessly through websites, social media, and WhatsApp groups. The bureaucratic structure of the Public Information and Documentation Officer (PPID) in Kraton Village is well-defined, although there is a significant dependence on a few individuals. There is a need for clearer and more systematic Standard Operational Procedures (SOPs) in managing information. From the perspective of Collaborative Governance in KIP, Kraton Village showcases remarkable advancements in transitioning to electronic governance despite limited resources. The design of institutions and the collaborative processes between the village government and the community are focal points. Facilitative leadership from the village government is essential in fostering an environment that supports information transparency. This research underscores the paramount importance of collaborative governance in the implementation of public information transparency through electronic government. It highlights the pressing necessity for clear SOPs and systematic information management to significantly enhance governance quality and community engagement in Kraton Village. The study offers a new perspective on implementing e-government and KIP in rural settings, illustrating how technological adaptation and collaboration can effectively address geographical and resource limitations. These findings are not just relevant, but crucial for other village governments encountering similar circumstances, providing invaluable insights for the design and execution of effective e-Government strategies.